Melatonin Attenuates Ischemia/Reperfusion-Induced Oxidative Stress by Activating Mitochondrial Fusion in Cardiomyocytes. (10th January 2022) - Ma, Xiaoling; Wang, Shengchi; Cheng, Hui; Ouyang, Haichun; Ma, Xiaoning
Abstract : Myocardial ischemia/reperfusion (I/R) injury can stimulate mitochondrial reactive oxygen species production. Optic atrophy 1- (OPA1-) induced mitochondrial fusion is an endogenous antioxidative mechanism that preserves the mitochondrial function. In our study, we investigated whether melatonin augments OPA1-dependent mitochondrial fusion and thus maintains redox balance during myocardial I/R injury. In hypoxia/reoxygenation- (H/R-) treated H9C2 cardiomyocytes, melatonin treatment upregulated OPA1 mRNA and protein expression, thereby enhancing mitochondrial fusion. Melatonin also suppressed apoptosis in H/R-treated cardiomyocytes, as evidenced by increased cell viability, diminished caspase-3 activity, and reduced Troponin T secretion; however, silencing OPA1 abolished these effects. H/R treatment augmented mitochondrial ROS production and repressed antioxidative molecule levels, while melatonin reversed these changes in an OPA1-dependent manner. Melatonin also inhibited mitochondrial permeability transition pore opening and maintained the mitochondrial membrane potential, but OPA1 silencing prevented these outcomes. These results illustrate that melatonin administration alleviates cardiomyocyte I/R injury by activating OPA1-induced mitochondrial fusion and inhibiting mitochondrial oxidative stress.